Immersion with robots in large virtual environments - Xie, Xianshi; Lin, Qiufeng; Wu, Haojie; Adams, Julie A.; Bodenheimer, Bobby E. (2012 7th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2012)
This paper presents a mixed reality system for combining real robots, humans, and virtual robots. The system tracks and controls physical robots in local physical space, and inserts them into a virtual environment (VE). The system allows a human to locomote in a VE larger than the physically tracked space of the laboratory through a form of redirected walking. An evaluation assessed the conditions under which subjects found the system to be the most immersive.